A red mud-based PBAs-derived metal oxide Fenton catalyst and its preparation method and application

By reacting the iron -rich part of the red mud with the transition metal salt and potassium ferrous cyanide, the PBAS derivative metal oxides are generated as high -efficiency fenton catalysts to solve the problem of low mud utilization and difficulty in dye wastewater treatment. It achieves low -cost, efficient catalyst preparation and degradation effects of dye wastewater.

CN116139863BActive Publication Date: 2025-01-28CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310005891.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-01-28
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

In the prior art, red mud utilization rate is low, advanced oxidation process catalysts are costly, difficult to recover, secondary pollution exists, and dye-containing wastewater is difficult to treat.

Method used

By reacting the iron -rich part of the red mud with the transition metal salt and potassium ferrous cyanide, the PBAS derivative metal oxides are generated as high -efficiency fenton catalysts, and H2O2 is used to treat dye wastewater.

Benefits of technology

The efficient resource utilization of red mud is realized, and the catalysts that are low -cost, excellent performance, and reused can be used to effectively degrade the dye wastewater and avoid secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116139863B_ABST
    Figure CN116139863B_ABST
Patent Text Reader

Abstract

The invention discloses a red mud-based PBAs-derived metal oxide Fenton catalyst and a preparation method and application thereof, belonging to the technical field of iron-based Fenton catalysts. Red mud is added to deionized water, and hydrochloric acid is added after dispersion; after sufficient reaction, a transition metal salt is added, and potassium ferrocyanide solution is added dropwise after stirring and dissolving; after stirring and sufficient reaction, solid-liquid separation and washing are performed, and the obtained solid material is roasted to obtain a catalyst. Under the conditions of a catalyst concentration of 0.05-2g / L, a H2O2 concentration higher than 0.5mM, a pollutant concentration of 50ppm, an initial pH of 3-11 and a temperature of 30°C, more than 90% of the reactive black 5 dye (RB5) can be degraded within 5-30min. The method of the invention can develop an efficient red mud-based catalyst, improve the utilization rate of red mud, achieve efficient purification of organic wastewater, and achieve waste treatment with waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of iron-based Fenton catalysts, and in particular relates to a red mud-based PBAs-derived metal oxide high-efficiency Fenton-like catalyst, a preparation method thereof, and an application thereof. Background Art

[0002] Red mud is a highly alkaline solid waste. Due to its low utilization rate, it is mainly stored in large quantities, occupying a large amount of land and causing certain harm to the surrounding ecology. Red mud contains a large amount of iron, so an important direction for the resource utilization of red mud is to recover the iron and use it as an iron-based catalytic material. At present, the application ideas of red mud iron-based catalytic materials are mainly to reduce the alkalinity of the material, increase the reaction active sites, increase the specific surface area and strengthen the Fe cycle. The main approaches include dealkalization / modification after dealkalization, or the preparation of ZVI using red mud, loading / doping and adding external reducing agents, all of which have achieved certain results. However, in order to be able to adapt to different pollutants and actual wastewater and achieve large-scale application, more types of high-efficiency red mud-based catalysts need to be developed.

[0003] Printing and dyeing wastewater is one of the most difficult industrial wastewaters to treat, with an annual discharge volume of approximately 1.6 billion tons. If not treated to meet standards, it can harm natural water bodies and organisms. Advanced oxidation processes offer the advantages of milder reactions, simplicity, and high efficiency compared to traditional physical, chemical, and biological treatment processes. However, there is a need to develop more catalysts with superior catalytic performance, low cost, environmental friendliness, strong reusability, and ease of recycling to meet practical applications.

[0004] Prussian blue and its analogues are a common class of iron-based MOFs materials that can be easily synthesized at room temperature. They have the advantages of adjustable composition / structure, large specific surface area and porosity, and rich active sites, and have good application prospects in the field of advanced oxidation. If the material is calcined, the resulting metal oxide not only inherits its structural advantages, but is also said to have strong magnetism and stability, which is conducive to recycling and reuse. Based on this, the applicant proposed a method of preparing low-cost PBAs-derived metal oxides using the iron-rich characteristics of red mud, improving the resource utilization of red mud, and using it as a Fenton-like catalyst to activate H2O2 to treat dye wastewater, thereby achieving waste treatment. Summary of the Invention

[0005] The purpose of the present invention is to provide a red mud-based PBAs-derived metal oxide high-efficiency Fenton-like catalyst and its preparation method and application, mainly to solve the current problems of low red mud utilization, high cost of advanced oxidation process catalysts, difficulty in recovery, secondary pollution, and difficulty in treating dye-containing wastewater.

[0006] The purpose of the present invention is to be achieved by the following steps:

[0007] A method for preparing a red mud-based PBAs-derived metal oxide Fenton catalyst comprises the following steps: adding red mud to deionized water, dispersing the red mud, and then adding acid; adding a transition metal salt after sufficient reaction, stirring and dissolving the salt, and then adding a potassium ferrocyanide solution dropwise; stirring and reacting the salt, separating the solid from the liquid, washing the salt, and roasting the obtained solid.

[0008] The ratio of the volume of deionized water to the amount of red mud added is (15-150) mL: (1-10) g.

[0009] The acid includes: hydrochloric acid, sulfuric acid or nitric acid; preferably hydrochloric acid, the concentration of hydrochloric acid is 5-7 mol / L, and the volume ratio of hydrochloric acid to red mud solution is (2.4-24): (15-150). The reaction temperature and time after adding hydrochloric acid are 80-95°C and 5-7h respectively.

[0010] The purpose of adding acid in the present invention is to dealkalize and dissolve the iron in the red mud, but hydrochloric acid is preferred here because it is volatile and will not affect the composition or performance of the material in the later stage.

[0011] The transition metal salt comprises at least one of cobalt chloride, copper chloride, cerium chloride and manganese chloride, and the amount thereof is 0.002-0.16 mol: (1-10) g red mud.

[0012] The mass ratio of the potassium ferrocyanide molar mass to the red mud is 0.00748-0.3548 mol: (1-10) g, the volume of the potassium ferrocyanide solution is 15-150 mL, and the dropping speed is 5-10 min / mL.

[0013] The purpose of adding potassium ferrocyanide in the present invention is to react with the iron dissolved in the red mud and the added transition metal to form PB or PBAs. If the potassium ferrocyanide is added too quickly, the reaction between the potassium ferrocyanide, the iron and the added transition metal may be uneven, resulting in the formed PBAs containing no or only the iron in the red mud, failing to achieve the purpose of the compound containing both the iron dissolved in the red mud and other transition metals.

[0014] Add potassium ferrocyanide and stir the reaction for 10-14 hours.

[0015] The calcination temperature is 300-700°C and the time is 1-3h.

[0016] The present invention also provides a red mud-based PBAs-derived metal oxide Fenton catalyst prepared by the method.

[0017] The present invention also provides an application of the red mud-based PBAs-derived metal oxide Fenton catalyst, which is characterized in that it is used for adsorption and / or catalytic treatment of dye wastewater, especially H2O2 degradation of dye wastewater.

[0018] The dye is Reactive Black 5, and the initial concentration is 50 ppm.

[0019] The catalyst concentration in the degradation system is 0.05-2 g / L, the H2O2 concentration is higher than 0.5 mM, the initial pH is 3-11, the temperature is 25-35° C., and the shaking speed is 150-250 rpm.

[0020] The present invention preferably specifically comprises the following steps:

[0021] (1) Add 1-10 g of red mud to a conical flask containing 15-150 mL of deionized water, disperse by ultrasonication for 10 min, add 2.4-24 mL of 6 mol / L hydrochloric acid, react at 90 °C for 6 h, add 0.002-0.16 mol of cobalt chloride and other transition metal salts to fully dissolve, add 15-150 mL of a solution containing 0.00748-0.3548 mol of potassium ferrocyanide dropwise, stir and react for 12 h, collect by centrifugation and wash, and calcine the obtained solid material in a muffle furnace at 300-700 °C for 2 h to finally obtain a high-efficiency Fenton-like catalyst derived from red mud-based PBAs.

[0022] (2) The degradation system has a Reactive Black 5 concentration of 50 ppm, a catalyst concentration of 0.05 to 2 g / L, an H2O2 concentration greater than 0.5 mM, an initial pH of 3 to 11, a temperature of 30°C, a degradation time of 30 min, and a shaker speed of 200 rpm. Every 5 to 10 minutes, a certain amount of the reaction solution is withdrawn from the degradation system to measure the concentration of the remaining Reactive Black 5.

[0023] The present invention utilizes red mud for the first time to prepare PBA-derived metal oxides, obtaining a catalyst with low cost, good performance and strong reusability, thereby improving the utilization of red mud while purifying organic wastewater, achieving waste treatment with waste.

[0024] The present invention effectively activates H2O2 and efficiently degrades Reactive Black 5 dye by adding only a small amount of transition metal. This demonstrates that the catalyst obtained by the present invention has the advantages of low cost and high efficiency, greatly improving the utilization of red mud and providing a new, economical and effective catalyst for the purification of organic wastewater.

[0025] This invention utilizes red mud to prepare a highly efficient Fenton-like catalyst composed of red mud-based PBAs-derived metal oxides (RM-PBAs-MO). This catalyst is simple to synthesize, low-cost, lacks the strong alkalinity of red mud, and possesses abundant active sites and water stability. It has excellent purification effects on dye wastewater and promising application prospects in the field of advanced oxidation, facilitating the large-scale application of red mud. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1The adsorption (left) and degradation curves (right) of Reactive Black 5 of Example 1 and Comparative Example are shown.

[0027] Figure 2 The adsorption (left) and degradation curves (right) of Reactive Black 5 of Example 2 and the comparative example are shown.

[0028] Figure 3 The adsorption (left) and degradation curves (right) of Reactive Black 5 of Example 3 and Comparative Example are shown.

[0029] Figure 4 The adsorption (left) and degradation curves (right) of Reactive Black 5 of Example 4 and Comparative Example are shown.

[0030] Figure 5 The degradation curves of Reactive Black 5 under different pH conditions.

[0031] Figure 6 The following are XRD analysis patterns of the materials used in the examples and comparative examples. DETAILED DESCRIPTION

[0032] The following specific examples or implementation modes are intended to further illustrate the present invention rather than to limit the present invention.

[0033] Example 1

[0034] The method described in this embodiment is mainly carried out according to the following steps:

[0035] (1) Take 5g of red mud and place it in a beaker filled with 75mL of deionized water. Ultrasonic dispersion is performed for 10min. Then 12mL of 6mol / L hydrochloric acid is added and shaken at 90℃ for 6h. Then 0.01mol of cobalt chloride is added and stirred for 5min. While stirring, 75mL of 0.0374mol potassium ferrocyanide solution is added dropwise at a rate of 8min / mL. After addition, stirring is continued for 12h. After centrifugal cleaning, vacuum drying is performed to obtain red mud-based PBAs material. The red mud-based PBAs material is placed in a muffle furnace and calcined at 500℃ for 2h to obtain a stable RM-0.01M Co-PBAs-MO material.

[0036] (2) The pH of a 50 ppm Reactive Black 5 solution was adjusted to 3.0 using 0.1 mol / L sulfuric acid, and 100 mL was then poured into a 250 mL conical flask. 0.01 g RM-0.01 M Co-PBAs-MO was added to the reaction solution and adsorption was performed in a shaker at 200 rpm and 30°C. After 30 minutes, 6 mM H2O2 was added to the system to initiate the degradation reaction, and the reaction time was 30 minutes.

[0037] (3) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0038] Conclusion: If Figure 1 As shown in the data, compared with red mud and undoped Co materials, RM-0.01M Co-PBAs-MO doped with 0.01M Co has a better adsorption effect on Reactive Black 5 dye; the degradation effect is more significantly improved. Under the conditions of catalyst concentration = 0.1g / L, H2O2 concentration = 6mM, Reactive Black 5 concentration = 50ppm, initial pH = 3, and temperature = 30℃, the degradation rate reached 86.24% within 5min, while the degradation rates of red mud and undoped Co red mud-based PB-MO were only 3.66% and 3.80%.

[0039] Example 2

[0040] The method described in this embodiment is mainly carried out according to the following steps:

[0041] (1) Take 5g of red mud and place it in a beaker filled with 75mL of deionized water. Ultrasonic dispersion was performed for 10min. Then 12mL of 6mol / L hydrochloric acid was added and shaken at 90℃ for 6h. Then 0.02mol of cobalt chloride was added and stirred for 5min. While stirring, 75mL of 0.0574mol of potassium ferrocyanide solution was added dropwise. After adding, the mixture was stirred for 12h. After centrifugal cleaning, vacuum drying was performed to obtain red mud-based PBAs material. The red mud-based PBAs material was placed in a muffle furnace and calcined at 500℃ for 2h to obtain a stable RM-0.02MCo-PBAs-MO material.

[0042] (2) A 50 ppm Reactive Black 5 solution was adjusted to pH 3.0 using 0.1 mol / L sulfuric acid, and 100 mL was then poured into a 250 mL conical flask. 0.01 g RM-0.02 M Co-PBAs-MO was added to the reaction solution and adsorption was performed in a shaker at 200 rpm and 30°C. After 30 minutes, 6 mM H2O2 was added to the system to initiate the degradation reaction, and the reaction time was 30 minutes.

[0043] (3) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0044] Conclusion: If Figure 2As shown in the data, compared with red mud and undoped Co materials, RM-0.02M Co-PBAs-MO doped with 0.02M Co has a better adsorption effect on Reactive Black 5 dye; the degradation effect is more significantly improved. Under the conditions of catalyst concentration = 0.1g / L, H2O2 concentration = 6mM, Reactive Black 5 concentration = 50ppm, initial pH = 3, and temperature = 30℃, the degradation rate reached 96.03% within 5min, while the degradation rates of red mud and undoped Co red mud-based PB-MO were only 3.66% and 3.80%.

[0045] Example 3

[0046] The method described in this embodiment is mainly carried out according to the following steps:

[0047] (1) Take 5g of red mud and place it in a beaker filled with 75mL of deionized water. Ultrasonic dispersion was performed for 10min. Then 12mL of 6mol / L hydrochloric acid was added and shaken at 90℃ for 6h. Then 0.04mol of cobalt chloride was added and stirred for 5min. While stirring, 75mL of 0.0974mol of potassium ferrocyanide solution was added dropwise. After addition, stirring was continued for 12h. After centrifugal cleaning, vacuum drying was performed to obtain red mud-based PBAs material. The red mud-based PBAs material was placed in a muffle furnace and calcined at 500℃ for 2h to obtain a stable RM-0.04MCo-PBAs-MO material.

[0048] (2) A 50 ppm Reactive Black 5 solution was adjusted to pH 3.0 using 0.1 mol / L sulfuric acid, and 100 mL was then poured into a 250 mL conical flask. 0.01 g RM-0.04 M Co-PBAs-MO was added to the reaction solution and adsorption was performed in a shaker at 200 rpm and 30°C. After 30 minutes, 6 mM H2O2 was added to the system to initiate the degradation reaction, and the reaction time was 30 minutes.

[0049] (3) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0050] Conclusion: If Figure 3 As shown in the data, compared with red mud and undoped Co materials, RM-0.04Co-PBAs-MO doped with 0.04M Co has a better adsorption effect on Reactive Black 5 dye; the degradation effect is more significantly improved. Under the conditions of catalyst concentration = 0.1 g / L, H2O2 concentration = 6 mM, Reactive Black 5 concentration = 50 ppm, initial pH = 3, and temperature = 30°C, the degradation rate reached 86.48% within 5 minutes, while the degradation rates of red mud and undoped Co red mud-based PB-MO were only 3.66% and 3.80%.

[0051] Example 4

[0052] The method described in this embodiment is mainly carried out according to the following steps:

[0053] (1) Take 5g of red mud and place it in a beaker filled with 75mL of deionized water. Ultrasonic dispersion was performed for 10min. Then 12mL of 6mol / L hydrochloric acid was added and shaken at 90℃ for 6h. Then 0.08mol of cobalt chloride was added and stirred for 5min. While stirring, 75mL of 0.1774mol of potassium ferrocyanide solution was added dropwise. After addition, stirring was continued for 12h. After centrifugal cleaning, vacuum drying was performed to obtain red mud-based PBAs material. The red mud-based PBAs material was placed in a muffle furnace and calcined at 500℃ for 2h to obtain a stable RM-0.08MCo-PBAs-MO material.

[0054] (2) A 50 ppm Reactive Black 5 solution was adjusted to pH 3.0 using 0.1 mol / L sulfuric acid, and 100 mL was then poured into a 250 mL conical flask. 0.01 g RM-0.08 M Co-PBAs-MO was added to the reaction solution and adsorption was performed in a shaker at 200 rpm and 30°C. After 30 minutes, 6 mM H2O2 was added to the system to initiate the degradation reaction, and the reaction time was 30 minutes.

[0055] (3) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0056] Conclusion: If Figure 4 As shown in the data, compared with red mud and undoped Co materials, RM-0.08Co-PBAs-MO doped with 0.08M Co has a better adsorption effect on Reactive Black 5 dye; the degradation effect is more significantly improved. Under the conditions of catalyst concentration = 0.1 g / L, H2O2 concentration = 6 mM, Reactive Black 5 concentration = 50 ppm, initial pH = 3, and temperature = 30°C, the degradation rate reached 85.22% within 5 minutes, while the degradation rates of red mud and undoped Co red mud-based PB-MO were only 3.66% and 3.80%.

[0057] Example 5

[0058] The method described in this embodiment is mainly carried out according to the following steps:

[0059] (1) The pH of a 50 ppm Reactive Black 5 solution was adjusted to 3.0, 5.0, 7.0, 9.0, and 11.0 using 0.1 mol / L sulfuric acid. 100 mL of each solution was then poured into different 250 mL conical flasks. 0.1 g of RM-0.02 M Co-PBAs-MO was added to the reaction solution and adsorption was performed in a shaker at 200 rpm and 30°C. After 30 minutes, 20 mM H2O2 was added to the system to initiate the degradation reaction. The reaction time was 30 minutes.

[0060] (2) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0061] Conclusion: If Figure 5 As shown in the data, in the pH range of 3 to 11, red mud-based PBAs-MO doped with 0.02 M Co had a good catalytic effect. Under the conditions of catalyst concentration = 1.0 g / L, H2O2 concentration = 20 mM, active black 5 concentration = 50 ppm, and temperature = 30°C, the degradation rates obtained within 30 min were 95.84%, 94.96%, 94.48%, 93.83% and 91.46%, respectively.

[0062] Comparative Example 1

[0063] The method described in this embodiment is mainly carried out according to the following steps:

[0064] (1) Take 5g of red mud and place it in a beaker filled with 75mL of deionized water. Ultrasonic dispersion is performed for 10min. Then 12mL of 6mol / L hydrochloric acid is added and shaken at 90℃ for 6h. Then 75mL of 0.0174mol potassium ferrocyanide solution is added dropwise while stirring. After addition, stirring is continued for 12h. After centrifugal cleaning, vacuum drying is performed to obtain red mud-based PB material. The red mud-based PB material is placed in a muffle furnace and calcined at 500℃ for 2h to obtain a stable RM-PB-MO material.

[0065] (2) A degradation reaction was carried out by adding RM-PB-MO to the reaction system of Examples 1 to 4.

[0066] (3) Take 0.5 mL of the reaction solution every 5 to 10 minutes, then add 0.2 mL of tert-butyl alcohol for quenching, and then measure the concentration of the remaining Reactive Black 5 using a UV-visible spectrophotometer at a wavelength of 598 nm.

[0067] Conclusion: If Figure 1 or Figure 2 or Figure 3 or Figure 4As shown in the figure, the adsorption and degradation of Reactive Black 5 dye by RM-PB-MO without Co doping were not significantly improved. Under the conditions of catalyst concentration = 0.1 g / L, H2O2 concentration = 6 mM, Reactive Black 5 concentration = 50 ppm, initial pH = 3, and temperature = 30°C, the degradation rate obtained within 30 min was only 17.98%.

[0068] like Figure 6 As shown, the main phases of RM-0.01M Co-PBAs-MO, RM-0.02M Co-PBAs-MO, RM-0.04M Co-PBAs-MO, and RM-0.08M Co-PBAs-MO are cobalt iron oxides with spinel structure (Co 0.62 Fe 1.38 )FeO4, according to relevant literature, is a derivative material that inherits the topological structure of the PBA precursor, effectively synthesizing red mud-based PBAs before calcination. The primary iron-containing phase of the RM-PB-MO material is magma hematite, a result of high-temperature oxidation; whereas the primary iron-containing phase of red mud is hematite. This explains the similar performance of red mud and RM-PB-MO.

Claims

1. An application of a red mud-based PBAs-derived metal oxide Fenton catalyst, characterized in that: The preparation method of the red mud-based PBAs-derived metal oxide Fenton catalyst used for degrading active black 5 in the presence of H2O2 comprises the following steps: adding red mud to deionized water, adding acid after dispersion; adding transition metal salt after sufficient reaction, stirring and dissolving, and adding potassium ferrocyanide solution dropwise at a dropping speed of 5-10 min / mL; stirring and sufficient reaction, and solid-liquid separation and washing, and roasting the obtained solid material.

2. The use according to claim 1, characterized in that: The ratio of the volume of deionized water to the amount of red mud added is (15-150) mL: (1-10) g.

3. The use according to claim 1, characterized in that: The acid includes hydrochloric acid, sulfuric acid or nitric acid.

4. The use according to claim 3, characterized in that: The concentration of hydrochloric acid is 5-7 mol / L, and the volume ratio of hydrochloric acid to red mud solution is (2.4-24): (15-150). The reaction temperature and time after adding hydrochloric acid are 80-95°C and 5-7h, respectively.

5. The use according to claim 1, characterized in that: The transition metal salt comprises at least one of cobalt chloride, copper chloride, cerium chloride and manganese chloride, and the amount thereof is 0.002-0.16 mol: (1-10) g red mud.

6. The use according to claim 1, characterized in that: The mass ratio of the molar mass of potassium ferrocyanide to red mud is 0.00748-0.3548 mol: (1-10) g, and the volume of the potassium ferrocyanide solution is 15-150 mL.

7. The use according to claim 1, characterized in that: Add potassium ferrocyanide and stir the reaction for 10-14 h.

8. The use according to claim 1, characterized in that: The calcination temperature is 300~700 ℃ and the time is 1-3h.

9. The use according to claim 1, characterized in that: The catalyst concentration in the degradation system is 0.05-2 g / L, the H2O2 concentration is higher than 0.5 mM, the initial pH is 3-11, the temperature is 25-35°C, and the shaking speed is 150-250rpm.

Citation Information

Patent Citations

  • Modified red mud and preparation method and application thereof

    CN105107510A

  • Preparation method of porous FexCo3-xO4 nanocage, nanocage and application thereof

    CN106552628A